1989
DOI: 10.1161/01.res.65.3.591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phalloidin on structure and permeability of rete capillaries in the normal and hypoxic state.

Abstract: The effects of 10(-6) M phalloidin on reperfusion-injured blood capillary structure and permeability were studied in the countercurrent perfused rete mirabile of the eel swim bladder. In the normal rete, the addition of phalloidin to the perfusion medium did not induce morphological or functional changes. When flow was arrested for 30 minutes, during which time the capillaries were exposed to inhibitors of ATP generation, and flow was then resumed with an oxygenated medium, cell membrane blebs and vacuolizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The authors suggested that 5-HT helped to regulate endothelial junc tional stability by promoting actin filament formation and stability, as had been demonstrated by Montesano et al 25 for the phalloidin-mediated induction of tight junctional elements. Rasio et al 26 demonstrated that phalloidin pretreatment provided protection against structural and func tional damage induced by hyperoxia-reperfusion in rete capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that 5-HT helped to regulate endothelial junc tional stability by promoting actin filament formation and stability, as had been demonstrated by Montesano et al 25 for the phalloidin-mediated induction of tight junctional elements. Rasio et al 26 demonstrated that phalloidin pretreatment provided protection against structural and func tional damage induced by hyperoxia-reperfusion in rete capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Active capillary constriction has been demonstrated in rete capillaries, in the spleen and in the pancreas to occur to such an extent that red blood cell flow was impeded [1, 2, 3]. Similar observations have not, however, been made in the cardiac microvasculature, possibly as a result of the inaccessibility of the capillary bed to in vivo observation.…”
Section: Introductionmentioning
confidence: 92%
“…INTEGRITY of the filamentous (F)-actin structures in the vascular endothelium is necessary for its physiological functioning as a selectively permeable barrier (30,32,33,40). Increased permeability of the endothelial barrier provokes edema that can result in severe injury of the adjacent tissue.…”
mentioning
confidence: 99%